Strategi Manajemen Pemasaran Syariah pada BPR Arsindo Kediri di Era Disrupsi - Al Haris, Mohammad Basid; Ashari, Denny Rakhmad Widi; Rifa’i, Akhmad (SINDA: Comprehensive Journal of Islamic Social Studies, 2023)
In the 21st century, we are entering an era of uncertain disruption. This also changes the marketing strategy on the wheels of business. Because the pattern of consumer behavior is clearly different from the previous era. The challenge is the extent of consistency in the implementation of sharia marketing management. This is because the financial services industry is a business that requires a high level of trust. The basic concept of Baitul Maal (currently the financial services industry) is to store and distribute to customers. This is to develop the business wheel so that it continues to sustain growth. Then it is necessary Sharia marketing management. Goals, how the company's goals are achieved according to the target. The targeted Sharia marketing management strategy has an impact on consumer decisions in product transactions of the financial services industry. This journal research will discuss how the marketing management strategy of Artha Samudra Indonesia People's Bank (BPR Arsindo) Kediri deals with the challenges of consumer behavior patterns in the era of disruption. This journal research aims to identify and educate the public in increasing financial literacy.